Pengujian Kualitas Air Sumur di Daerah Pesisir dan Daratan Provinsi Papua Barat Daya - Rahmatullah, Azwar; Nurbia, Nurbia; abubakar, endang (Universitas Tanjungpura, 2025)
Water is a vital component for life on Earth. Currently, many people still struggle to access sufficient water due to limited availability. This research aims to determine the pH, TDS, salinity, conductivity, turbidity, TSS, and temperature of well water. The results of testing several physical parameters indicate the quality of well water in Pulau Doom and SP4, Sorong Regency. Measurements of pH, TDS, conductivity, salinity, turbidity, and temperature of the tested well water samples did not meet the quality standards set forth in the Ministry of Health Regulation Number 2 of 2023 concerning Environmental Health. The average pH level of the well water was 8.2, while the values for TDS, salinity, and conductivity were 0. The turbidity measurement was 0.26 NTU (still above the standard). Based on the initial testing, it can be concluded that filtration and treatment, such as boiling, are necessary to minimize the negative impacts of consuming well water. The second test was conducted to identify the quality of the dam water in SP4, Sorong Regency, to determine its suitability for use. This test used physical and chemical parameters measured with a pH meter, AMT03 AMTAST pH/EC/TDS Meter, and TSS LH-XZ03 Turbidity Meter, which provide direct and concrete data. The testing technique involved laboratory measurements. However, both water sources still meet the drinking water quality standards specified in the Ministry of Health Regulation Number 2 of 2023.